Conference report. Global Asbestos Congress (GAC 2004), November 19-21, 2004, Tokyo, Japan - Kazan-Allen, Laurie (London, 2005)
"The global campaign to ban asbestos took a giant leap forward with the success of the Global Asbestos Congress 2004 (GAC). The attendance of representatives from 40 countries, the presence of distinguished international speakers, the interest of Japanese, Belgian, Brazilian and South African media teams and the continual discussions in hallways and at social events were physical manifestations of an unquantifiable “buzz” generated by bringing together so many people affected by asbestos. From the comprehensive agenda to the bell ringing protocol to the identifying white jackets worn by the scores of volunteers, the conference had been expertly planned by the GAC Organizing Committee; since 2002, committee members had worked assiduously to generate political backing and raise funds for this landmark event, the first global conference to focus on the repercussions of asbestos use in Asia."